Analysis of adverse drug reactions/events of cancer chemotherapy and the potential mechanism of Danggui Buxue decoction against bone marrow suppression induced by chemotherapy - Yu, Bin; Yan, Xida; Zhu, Yuanying; Luo, Ting; Sohail, Muhammad; Ning, Hong; Xu, Hui (Frontiers in Pharmacology, 2023)
To analyze the clinical characteristics of adverse reactions/events based on chemotherapy in cancer patients, and then explore the potential mechanism of Danggui Buxue Decoction (DBD) against chemotherapy-induced bone marrow suppression (BMS).Retrospectively collected and evaluated were the clinical data of patients in a hospital who experienced adverse reactions/events brought on by chemotherapeutic medications between 2015 and 2022. We explored the potential mechanism of DBD against BMS using network pharmacology based on the findings of the adverse reactions/events analysis.Results: 151 instances (72.25%) experienced adverse reactions/events from a single chemotherapy medication. Besides, platinum-based medications produced the most unfavorable effects. The study also found that chemotherapy caused the highest number of cases of BMS, including platinum drugs. Consequently, BMS is the most prevalent adverse reaction disease caused by chemotherapy found in this part.According to network pharmacology findings, DBD can prevent BMS primarily involving 1510 primary targets and 19 key active ingredients. Based on the enrichment analysis, PI3K-AKT, TNF, MAPK, and IL-17 signaling pathways made up the majority of the DBD-resisting BMS pathways. Molecular docking displayed that kaempferol, the major active ingredient of DBD, had the highest binding energy (-10.08 kJ•mol -1 ) with PTGS2 (a key target of BMS).Cancer patients who received chemotherapy had a risk to develop BMS.Regular blood tests should be performed while taking medicine; early discovery and treatment can reduce a patient's risk of experiencing adverse reactions/events. Additionally, this study demonstrated that DBD, through a variety of targets and pathways, may be crucial in avoiding BMS.